The 12-week year : get more done in 12 weeks than others do in 12 months - Moran, Brian, 1959- (Wiley, 2013)
The guide to shortening your execution cycle down from one year to twelve weeks Most organizations and individuals work in the context of annual goals and plans; a twelve-month execution cycle. Instead, The 12 Week Year avoids the pitfalls and low productivity of annualized thinking. This book redefines your ""year"" to be 12 weeks long. In 12 weeks, there just isn't enough time to get complacent, and urgency increases and intensifies. The 12 Week Year creates focus and clarity on what matters most and a sense of urgency to do it now. In the end more of the impor.